Past, Present and Future of Democracy - Policy Review - Wolfgang Merkel (Past, Present and Future of Democracy - Policy Review, 2019)
The EU's framework programmes for research and innovation have devoted significant investments towards the study of democracy. This review presents findings from framework programme projects and in general takes stock of European research on the subject matter. It provides a mapping of results, evidence and recommendations, and assesses the needs and pertinent foci for future European research. It aims to build on areas of research where there is already a good deal of knowledge. At the same time, it focuses on those areas where there are gaps in our knowledge about the workings of and present threats to democracy.
Keywords: 330; democracy; political situation; populism; research